2008
DOI: 10.1186/1471-2458-8-370
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption patterns in the Waterloo Region, Ontario, Canada: a cross-sectional telephone survey

Abstract: Background: The demographics and lifestyles of Canadians are changing, thereby influencing food choices and food preparation in the home. Although different dietary practices are associated with increased risk of foodborne illness, our ability to evaluate food consumption trends and assess risks associated with foodborne illness is limited by lack of data on current eating habits and consumer food safety practices. The objective of this study was to describe, for the first time, the food consumption patterns i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…For the demographic characteristic risk factors, other studies [61,62] have found similar results in meat consumption among adults and single people; however, males were more likely to be consumers, which is associated with masculinity and power according to Rozin et al . [63].…”
Section: Discussionmentioning
confidence: 68%
“…For the demographic characteristic risk factors, other studies [61,62] have found similar results in meat consumption among adults and single people; however, males were more likely to be consumers, which is associated with masculinity and power according to Rozin et al . [63].…”
Section: Discussionmentioning
confidence: 68%
“…In 2008 sampling shifted to skinless chicken breasts, to reflect human consumption practices (Nesbitt et al, 2008). No difference in Salmonella prevalence was observed between skin-on and skinless chicken breasts (Cook et al, 2012).…”
Section: Qualitative Results: Retrospective Narrativesmentioning
confidence: 98%
“…Information on soy consumption is well known in Asia (Chen et al, 1999), where Chinese women aged 41-50 years had lower consumption compared with both younger and older women (Sadeghian et al, 2015). In Canada, although soymilk and tofu consumption rates were generally low among respondents, elderly individuals showed the highest soymilk consumption rate, and tofu consumption rate was highest among individuals between 25 and 54 years of age (Nesbitt et al, 2008).…”
Section: Discussionmentioning
confidence: 94%